1971
DOI: 10.1057/palgrave.jibs.8490732
|View full text |Cite
|
Sign up to set email alerts
|

Bias Phenomena Attendant to the Marketing of Foreign Goods in the U.S.

Abstract: When entering foreign markets, sellers face quotas, tariffs, and nontariff barriers. In addition, they may face an intangible barrier in the form of consumer bias on the basis of product origin. Since 1965 several articles have appeared dealing with bias phenomena and with the efficacy of marketing strategies designed to avoid, accommodate, or circumvent consumers' negative predispositions.The first study reported dealt with product bias and predilection in the Central American Common Market (CACM).1 Guatemala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
4
8

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(208 citation statements)
references
References 0 publications
8
184
4
8
Order By: Relevance
“…The research of this phenomenon in Serbia in 2015 showed that men were more ethnocentric (Marinkovic et al, 2011, Gasevic et al, 2015, Grubor & Đokic, 2015. Schooler (1971) and Dornoff et al (1974) stated that women had a more favourable assessment of products coming from abroad in comparison to men. Based on the previous statements, and primarily relying on the results of the research in Serbia, the following hypothesis is defined: H2: Men are more ethnocentric in comparison to women.…”
Section: Theoretical Framework Of the Researchmentioning
confidence: 99%
“…The research of this phenomenon in Serbia in 2015 showed that men were more ethnocentric (Marinkovic et al, 2011, Gasevic et al, 2015, Grubor & Đokic, 2015. Schooler (1971) and Dornoff et al (1974) stated that women had a more favourable assessment of products coming from abroad in comparison to men. Based on the previous statements, and primarily relying on the results of the research in Serbia, the following hypothesis is defined: H2: Men are more ethnocentric in comparison to women.…”
Section: Theoretical Framework Of the Researchmentioning
confidence: 99%
“…A common separation of the stage of development of a country is in More Developed Countries (MDC) and Less Developed Countries (LDC). Within this separation, products from industrial nations (MDC) are in principle more positive evaluated and are thus preferred products compare to products from non-industrial nations (LDC) (Amine et al, 2005;Schooler, 1971). In addition, a different image from a country over the time has been detected.…”
Section: Country-of-origin Effect: Values and Perceptionmentioning
confidence: 99%
“…Products sourced from developed countries are perceived as being superior to products originating from developing countries. Consumers consider the country's economic development when evaluating products sourced from foreign (Schooler, 1971;Bilkey & Nes, 1982;Han & Terpstra, 1988;Zain & Yasin, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%